Images reconstruction for well to well tomography with Levenberg Marquardt method - Chambi Chambi, Juan (2013)
The Cross-Borehole-Seismic Tomography is a seismic method most used for the determination of subsurface structure of the land. This method involves placing in a borehole the seismic wave generating sources, and in another borehole the receiver as waves detector. The tomographic image reconstructed from Cross-Borehole-Seismic Tomography is obtained by considering a parameter called slowness which is reverse speed with which the seismic waves travel, slowness S varies depending on the geological structure. We consider direct waves traveling from one borehole to another and we obtain an approximation of the following linear system as MS = T , where M is a matrix and is related to the discretization domain, S is the vector formed by the slowness of each discretized domain element and T is the arrival time of the first wave coming from source to detector. For the evaluation of the algorithms we design underground structures, which get the data from the detectors. To obtain more realistic data, we added random noise to 3.0%. With these data we proceed to rebuild the soil properties.